Adaptive system for wavefront correction of the PEARL laser facility. (December 2020) - Soloviev, A.A.; Kotov, A.V.; Perevalov, S.E.; Esyunin, M.V.; Starodubtsev, M.V.; Alexandrov, A.G.; Galaktionov, I.V.; Samarkin, V.V.; Kudryashov, A.V.; Ginzburg, V.N.; Korobeynikova, A.P.; Kochetkov, A.A.; et al.
Abstract: The results of the operation of a wavefront correction system based on a deformable bimorph mirror of the PEARL subpetawatt laser facility are presented. An improvement in the quality of focusing of laser radiation, which led to an increase in the Strehl ratio from 0.3 to 0.6, is demonstrated. The features of the compensation for phase distortions of the wavefront in the case of a low pulse repetition rate, as well as the correct allowance for the noise of the CCD camera when calculating the Strehl ratio are investigated.